If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 35 = -1x Reorder the terms: 35 + 6x = -1x Solving 35 + 6x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 35 + 6x + x = -1x + x Combine like terms: 6x + x = 7x 35 + 7x = -1x + x Combine like terms: -1x + x = 0 35 + 7x = 0 Add '-35' to each side of the equation. 35 + -35 + 7x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + 7x = 0 + -35 7x = 0 + -35 Combine like terms: 0 + -35 = -35 7x = -35 Divide each side by '7'. x = -5 Simplifying x = -5
| 8x+9=12x-5 | | 6v+14=8v+24 | | 12-1/3= | | -2x+1-(-3x+3)=-4+(x-2) | | 12r=18(r+.5) | | -5x+2=10-8x | | r=6(r+.5) | | .3333x+5=.16666(2x-5) | | 12x-3y-10= | | Inx-in(x+3)=6 | | Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= | | r=3(r+.5) | | 11/3×4/9 | | 6-9-(-6)= | | x-2y+74=0 | | 4/9×n=11/3 | | .8=.2+x-0.15 | | 3/100=n/660 | | x+5(x-5)=11 | | 3g+2g+5=0 |